Effect of the Sin Acoso program on the reduction of sexual harassment in schools, Trujillo-2022 (LACCEI, 2024)
The study made it possible to measure the effect of the "No to harassment" program on students' attitudes towards sexual harassment Trujillo-2022. Methodologically, a quantitative approach was used, whose design was experimental, of the experimental type, using the survey technique and the questionnaire as an instrument. The population consisted of 232 students of the sixth cycle of the Educational Institution, N°13003 "Virgen del Carmen". It is concluded that: (1) The students' attitudes towards sexual harassment after the application of the "No Harassment" program showed a significant change (p=0.0056370.05), evidencing a significant difference in the scores obtained between the evaluation phase (before and after the application), therefore, the program had a significant influence on the students' attitudes towards sexual harassment. (2) In the dimension Behaviors of a sexual nature, a Wilcoxon test significance p-value (p=0.002630.05) was evidenced in the comparison of scores (before and after) of the program implementation, consequently, the program had a positive effect. (3) In contrast, a p-value of significance was found in the dimensions Behaviors of a sexist nature (p=0.410838>0.05) as well as in the dimension Myths about Sexual Harassment (p=0.137252>0.05), thus establishing that the program did not have a significant influence. ey words: sexual harassment, no harassment, secondary education, attitudes towards sexual harassment.